Phylogeography of the Cow Knob Salamander (Plethodon punctatus Highton): populations on isolated Appalachian mountaintops are disjunct but not divergent - Graham, Matthew R.; Flint, William D.; Powell, Alexsis M.; Fet, Victor; Pauley, Thomas K. (Frontiers in Amphibian and Reptile Science, 2023)
Although many studies have examined how taxa responded to Pleistocene climate fluctuations in the Appalachian Mountains, impacts on high-elevation endemics of Central Appalachia are not yet understood. We use mitochondrial (ND4 & Cytb) and nuclear (GAPD) DNA sequences to investigate the phylogeography of the Cow Knob Salamander (Plethodon punctatus), a woodland species from Central Appalachian highlands thought to have origins in the Pleistocene. Data from 72 tail tips representing 25 sites revealed that the species comprises two geographically cohesive mitochondrial clades with a narrow, putative contact zone on Shenandoah Mountain. Molecular clock estimates indicate the clades diverged in the Middle Pleistocene. The population size of the Southern clade appears to have remained stable for at least 50,000 years. Despite spanning several isolated mountain systems, the Northern clade has exceptionally low genetic diversity, probably due to recent demographic expansion. Palaeodemographic hypothesis testing supported a scenario in which a founder effect characterized the Northern clade as it diverged from the Southern clade. Species distribution models predicted no suitable habitat for the species during the Last Glacial Maximum. Ultimately, Pleistocene glacial climates may have driven the species from the northern half of its current range, with recolonization events by members of the Northern clade as climates warmed. Density dependent processes may now maintain a narrow contact zone between the two clades.